Association Between Incense Burning and the Risk of Lung Cancer in Asian Population : Meta-Analysis of Nine Case–Control Studies - Hui Wen, Tang; Fui Ling, Voon; Edmund Ui Hang, Sim (Wiley, 2024)
Background: Various studies have explored the potential association between incense burning and the risk of lung cancer. However, the findings from these studies have been inconsistent. Objectives: This study aimed to provide a more comprehensive understanding of the relationship between incense burning and lung cancer risk in the Asian population through a meta-analysis. Methods: This meta-analysis, which includes nine case–control studies conducted in Asia and identified through Google Scholar, PubMed, and ScienceDirect up to January 7, 2024, was performed to evaluate the relevant literature. Using a fixed-effects model, the pooled odds ratio (OR) was calculated to determine the overall association between incense burning and lung cancer. Results: The results of the meta-analysis revealed a significant association between incense burning and the development of lung cancer (pooled OR = 1.33, 95% confidence interval [CI]: 1.20–1.48). Furthermore, a subgroup analysis was conducted based on smoking status. It was found that ever-smokers had a significantly higher risk of developing lung cancer when exposed to incense burning (pooled OR = 1.34, 95% CI: 1.09–1.65). Both hospital-based case–control studies (pooled OR = 1.28, 95% CI:1.10–1.48) and population-based case–control studies (pooled OR = 1.39, 95% CI: 1.21–1.60) yielded significant associations be-tween incense burning and lung cancer. Limitations of this study include the lack of detailed histologic information in most of the selected studies, highlighting the need for future research to include cohort studies that can more accurately assess the association between incense smoke inhalation and specific lung cancer subtypes. Conclusion: In conclusion, the findings of this meta-analysis, based on nine case–control studies, suggest that the risk of developing lung cancer among Asians may increase with exposure to incense burning.